Immediate hemodynamic changes after revascularization of complete infrarenal aortic occlusion: A classic issue revisited. (February 2016) - Georgakarakos, Efstratios; Argyriou, Christos; Georgiadis, George S.; Ioannou, Christos V.; Lazarides, Miltos K.
Abstract: Chronic total occlusion of the infrarenal aorta (CTOA) is a rare disease, characterized by severe impairment of limb perfusion. It is advocated that revascularization may improve survival rates, presumably due to improved cardiovascular performance; however no experimental or clinical data exist to identify a clear causative correlation and provide a relevant pathophysiologic background. Therefore we conducted a pilot study based on pulse wave analysis to detect the hemodynamic changes immediately after revascularization, in a group of six consecutive patients with CTOA. All patients were subjected to non-invasive measurements 1 day before surgery and at the end of the 1st postoperative month. Pulse wave analysis was performed noninvasively with a novel validated brachial cuff-based automatic oscillometric device. All patients had markedly preoperative high Augmentation Index (adjusted at heart rate 75 beats/min, AI@75). The AI@75 decreased from 46 ± 6.6 preoperatively to 24 ± 5.7 ( p 0.0002). Wave reflection magnitude decreased from 72.3 ± 5.2% to 63 ± 6.7% ( p 0.02). Cardiax index increased from 2.8 ± 1.2 to 3.4 ± 1.2 l/min × 1/m 2 ( p 0.41). Pulse wave velocity remained practically unchanged post-interventionally. These findings show that central aorta hemodynamics can be improved immediately following revascularization procedures in patients with complete occlusion of the entire length of the infrarenal aorta and can constitute the background of improved postoperative life-expectancy.